ANALISIS KEBERLANJUTAN KAWASAN MINAPOLITAN BUDIDAYA DI DESA SARASA KECAMATAN DAPURANG KABUPATEN MAMUJU UTARA - Arsyad, Iis (JSTT, 2016)
This study aimed to analyze the level of sustainability of aquaculture Minapolitan based in the Sarasa village Dapurang subdistrict, Mamuju Utara regency. The method used is RAPFISH analysis method using 5 dimensions of human resources, natural resources, institutional, technological and infrastructure. The results showed that the sustainability status Minapolitan based aquaculture in the Sarasa village Dapurang subdistrict, Mamuju Utara regency categorized quite sustainable because the resulting index value of 65.33. Status sustainability Sarasa Minapolitan in the village in terms of dimensions less sustainable technologies. Thus, the preparation and implementation of policies that can improve the condition of the sustainability of farming in the Sarasa village Minapolitan Dapurang subdistrict, Mamuju Utara regency deemed necessary.